GEOTECHNICAL ASSET MANAGEMENT FOR UK RAILWAY EMBANKMENTS - Siino, Giulia (2023)
The British railway system is one of the oldest in the world. Most railway embankments are aged around 150 years old and, the percentage of track disruption due to embankment failure is frequently higher than other types of railway infrastructure. Remarkable works have been done to understand embankment deterioration and develop asset modelling. Nevertheless, they do not represent a sufficient way of managing assets in detail. One of the biggest challenges that geotechnical asset managers and railway operator face is the detection of embankment failure at an early stage. Unplanned disruptions compromise safety for passengers, reliability of railway operators and require emergency budget deployment. To guarantee good system performance and meet costumer’s expectations, industries would benefit efficient and pro-active management activities and adoption of Geotechnical Asset Management (GAM) programs. To support the challenge, this research improves the understanding of the interaction between causes of embankment instability and visible signs of embankment instability. In this thesis, the signs of embankment instability are identified thanks to the use of a new metric called Embankment Instability Metric EIM developed by AECOM in 2018. The EIM measures the worsening of track geometry that is likely due to embankment instability. This research work presents the results of the analysis aiming to evaluate whether a link existed between track deterioration, due to embankment instability, and the geotechnical parameters known from literature as playing a role in the embankment disruption. Results of this analysis proved that, based on the specific analysis undertaken, different levels of correlation between causes and symptoms can be assessed and that some parameters show a better link with the EIM than others. The final outcome of this research work was the development of a decision-making tool based on a Multi-Criteria Decision-Making MCDM approach. The novel tool supports the decision-makers in the process of selecting the most appropriate intervention to be undertaken for a specific embankment asset given its current geotechnical conditions.